2012
DOI: 10.1021/jp303712y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Charge Transfer Dynamics in Photoexcited CdTe Quantum Dot Decorated on Graphene

Abstract: We report synthesis and ultrafast charge transfer dynamics of photoexcited CdTe quantum dots (QDs) decorated on graphene. We have synthesized CdTe QD particles of 2.2 nm sizes with first exciton (1S3/2-1Se) band ∼450 nm and then decorated the QD particles on graphene which has been confirmed by HRTEM studies. The CdTe QD decorated graphene has been named as G-CdTe. Steady state emission studies revealed that on the graphene surface CdTe emission gets quenched drastically which indicates the charge transfer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 24 publications
(46 reference statements)
4
68
0
Order By: Relevance
“…before their recombination in hybrid structures of CDs and semiconductor QDs, thus quenching the absorption and emission of semiconductor QDs. 23,38,39 The quenching efficiency of CDs is one order of magnitude higher than that of gold. 40 A similar mechanism may be responsible for the quenching of the CdTe QDs in this study.…”
Section: Resultsmentioning
confidence: 99%
“…before their recombination in hybrid structures of CDs and semiconductor QDs, thus quenching the absorption and emission of semiconductor QDs. 23,38,39 The quenching efficiency of CDs is one order of magnitude higher than that of gold. 40 A similar mechanism may be responsible for the quenching of the CdTe QDs in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The time‐resolved technique is a powerful experimental tool to investigate the dynamic properties of the photoinduced carriers in semiconductors, and has shown great potential for analyzing the photoinduced charge kinetics of graphene‐based nanomaterials. For instance, time‐resolved fluorescence spectroscopy has been extensively used for interface research on graphene‐semiconductor nanocomposites such as graphene/CdSe,101 graphene/CdS,97 and graphene/CdTe 102. Once combining graphene with the semiconductor, emission decay kinetics of the semiconductor nanocrystal decay much faster, and the photoluminescence (PL) lifetime of nanocomposites decreases with increasing graphene content, which is a direct proof of the electron transfer from the excited semiconductors to the graphene matrices.…”
Section: Graphene As An Electron Acceptor and Transportermentioning
confidence: 99%
“…Thus PL decay was dominated solely by the energy transfer pathway with prolonged irradiation. Transient absorption spectroscopy and transient photovoltage technique were also executed to understand the charge transfer dynamics of graphene‐semiconductor system including graphene/CdTe102 and graphene/CdS103 composites. The results demonstrated that the electron‐holes were separated efficiently by transferring photoinduced electrons from semiconductors to graphene, and the recombination of electron‐hole pairs in these excited semiconductor materials was retarded as well.…”
Section: Graphene As An Electron Acceptor and Transportermentioning
confidence: 99%
“…For example, it is now known that, after ultrafast photoexcitation of the electrons, energy relaxation occurs through mechanisms with markedly different time scales: first through energy redistribution by electron-electron scattering (∼10 fs), then thermalization with optical phonons (∼100 fs), and finally, anharmonic decay of optical phonons and/or coupling to substrate phonons (∼1 ps) [2][3][4]. More recently, ultrafast laser measurements have been used to probe the time scales of charge transfer to graphene from photoexcited adsorbed molecules [5]. However, experimentally the exact time scales and mechanisms associated with the adsorption and desorption of molecular species are not well known [6].…”
mentioning
confidence: 99%